Road Safety Analysis in the Central Region of Cuba - García Depestre, René (2025)
Traffic accidents are a global concern. They are the primary cause of death of children and young adults. Cuba is no exception. Villa Clara province, located in the central territory of Cuba, is identified as the region having the most unsafe roads. Thus, it is necessary to analyze the causes of accidents considering the information presented in accident reports. In this research, accident occurrence is characterized by using indices which reflect the vehicular composition of the traffic volume. These indices prove that the vehicle type classified as "other" (by the Cuban Highway Traffic Control Act) has a great influence in the occurrence of accidents due to speed differences and vehicular volume in relation to the rest of vehicle types. A riskiness scale is also established which is used to prioritize the road safety measures considering the risk, as well as the relationship between accident occurrence versus vehicular composition. Tne maintenance state of road infrastructure is also analized.